Exploring Public Speaking - Barton, Kris; Tucker, Barbara G. (Open textbook library., 2019)
In Exploring Public Speaking, especially in its second through fourth editions, we have attempted to create a usable, zero-cost textbook for basic public speaking courses or courses that include basic public speaking skills as one of their primary learning outcomes. The free, open nature of the text means that instructors are able to use all or part of it, and add their own materials. We believe this text addresses all the subjects that traditional publishers’ books would address in an appropriate writing style and with appropriate college-level learning theory in mind. The appendices address some additional topics that might be excluded from most texts, but that we believe add to the experience: learning theory, plagiarism, speaking online, speaking to diverse audiences, and humor in public speaking. In the third and fourth editions we have added “case study” examples and some different outline samples. We think this book is especially useful in coverage of PowerPoint, audience analysis and responsiveness, ethics in public speaking, persuasion, special occasion speeches, and structure of speeches. Because it was written by communication professors with decades of experience in the classroom, we are aware of the needs of basic public speaking students. Three ancillaries are currently available: electronic “flash cards” for study, PowerPoint slide decks on the 15 main chapters, and test banks for the 15 main chapters. As the website is developed, it will include videos of student speeches.